2018
DOI: 10.1371/journal.pone.0205734
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between socioeconomic status and weight gain during infancy: The BeeBOFT study

Abstract: BackgroundIncreased weight gain during infancy is a risk factor for obesity and related diseases in later life. The aim of the present study was to investigate the association between socioeconomic status (SES) and weight gain during infancy, and to identify the factors mediating the association between SES and infant weight gain.MethodsSubjects were 2513 parent-child dyads participating in a cluster randomized controlled intervention study. Family SES was indexed by maternal education level. Weight gain in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…People with a lower SES consume more of highcalorie food groups, such as carbohydrates, fats and sweets, and their food consumption pattern is less in harmony with food guidelines in terms of quality. People's nutritional knowledge also affects their consumption of F&V (Cotugna et al, 1992;Rutter, 2018;Wang et al, 2018). An interesting finding was that place of residence had the main contribution to F&V intake inequality (27.03%).…”
Section: Discussionmentioning
confidence: 99%
“…People with a lower SES consume more of highcalorie food groups, such as carbohydrates, fats and sweets, and their food consumption pattern is less in harmony with food guidelines in terms of quality. People's nutritional knowledge also affects their consumption of F&V (Cotugna et al, 1992;Rutter, 2018;Wang et al, 2018). An interesting finding was that place of residence had the main contribution to F&V intake inequality (27.03%).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to understand the mechanisms explaining socioeconomic inequalities in excess weight gain in early life and inform public health interventions, given that those children who experienced early rapid growth have a higher likelihood of developing childhood and later life OW/OB and adverse health outcomes 43 . A few studies have explored the mediators explaining socioeconomic inequalities in early rapid growth using the traditional regression-based methods to mediation analysis 40 , 42 and found that maternal smoking, maternal BMI, infant birth weight, gestational age at birth, maternal age and child-feeding practices mediated socioeconomic inequalities in early rapid growth. These studies have limitations in controlling for interactions between exposure and hypothesized mediators given that they have used traditional regression-based mediation analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, according to the Developmental Origins of Health and Diseases (DOHaD) hypothesis 37 , early-life factors including maternal weight status, maternal history of chronic diseases, smoking during pregnancy, and maternal nutrition 27 , 38 , 39 can play a role in increasing the risk of postnatal early rapid growth and subsequent OW/OB. Studies have documented socioeconomic inequalities in early growth 40 42 . Early rapid growth has also been found to be associated with an increased risk of childhood and later life OW/OB and adverse health outcomes 43 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although improvements in maternal education and income, reduction of fertility rate and maternal malnutrition and the expansion of health care services for pregnant women have promoted significant advances in reducing child undernutrition in Brazil, 28 this progress was not sufficient to overcome other forms of malnutrition 29 . Several studies have shown that poorer children have an increased risk for overweight, which is linked to a higher frequency of early weaning and introduction of age‐inappropriate types of food 30,31 . In addition, populations that have experienced long periods of extreme deprivation, such as those living in Northeast Brazil, tend to perceive childhood obesity not as a problem but as a sign of good health 32 .…”
Section: Discussionmentioning
confidence: 99%